THU0289 PREDICTORS AND SEVERITY OF POST-THROMBOTIC SYNDROME IN VASCULAR BEHÇET'S DISEASE: RETROSPECTIVE MULTICENTER STUDY. (2nd June 2020) - Aksoy, A.; Colak, S.; Yagiz, B.; Seniz, B. N.; Omma, A.; Yildiz, Y.; Atas, N.; Ilgin, C.; Sari, A.; Erden, A.; Karadag, O.; Dalkiliç, E.; et al.
Abstract : Background: Postthrombotic syndrome(PTS) defines chronic manifestations of venous insufficiency following deep vein thrombosis(DVT).It is the most frequent and disabling complication of DVT. Objectives: Aim of the study is to describe clinical characteristics and predictors of PTS, severe PTS among Behçet's disease(BD)patients with known low extremity DVT.Also, to depict venous Doppler ultrasonography(US)findings and its association with the clinical characteristic and treatments. Methods: This retrospective multicenter study included 205(166men, 39women;mean age 39±9.5 years)BD patients with DVT history.The Villalta scale was used to assess the presence and severity of PTS.Doppler US of bilateral legs are performed within 1 week of clinical evaluation.Total number of vessels with reflux, thrombi, recanalization and collaterals were calculated and presented as scores. Results: Of 205 BD patients with known DVT history; 127(62%) had PTS and 18% had severe PTS diagnosed by Villalta scale.(Table 1 ) Table 2 summarize multivariate logistic regression analyses for the risk of having PTS-moderate/severePTS. Severe PTS patients had increased reflux(p=.027) compared to mild group and decreased recanalization scores(p=.013)compared to moderate group(Figure1)Patients treated with AC+IS had increased recanalization(p:.078), collateral scores compared patients treated with only ISs(p=.004)(Figure2) Conclusion: After an acuteDVT, BD patients faced with high risk of having PTS, severe PTS.ISs decreases the risk of having PTS.Our results also suggest that AC treatment may decrease severity of PTS by increasing recanalization of thrombi. References: Disclosure of Interests: None declared